The Negative Impact of Single-Parent Families on Children in Tennessee Williams’ The Glass Menagerie and Marsha Norman’s ’night, Mother - Mahood Mohammed, Nidhal (International Journal of Psychosocial Rehabilitation, 2020)
Growing up in fatherless families has a negative impact on children. From a psychological point of view, single-parent children suffer from either self-alienation or social failure due to a sense of abandonment they experience in part of their life. In fact, the theme of parenthood attracted the attentions of many writers to show its negative impact on children whose fathers escaped their families forever. The study is associated with depicting the ways in which absent fathers are seen and how they shape the lives of their children as encoded in Tennessee Williams’ The Glass Menagerie and Marsha Norman’s ’night, Mother.